1996
DOI: 10.1002/cbf.692
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic fatty acid‐supported respiration in rats fed an energy‐dense diet

Abstract: The energy balance and hepatic fatty acid-supported respiration were studied in rats fed a control or an energy-dense diet. In addition, state 3 and 4 respiratory rates as well as ketone body production with palmitoylcarnitine as substrate were determined in isolated mitochondria. Metabolizable energy intake and energy expenditure increased in rats fed an energy-dense diet, but the gain in body weight and lipid content remained unchanged. No variation occurred in the mitochondrial palmitoylcarnitine utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…13 ± 15 We also suggested that a contribution to the increased energy expenditure could be given by the liver, as we found an increase in avin-adenine dinucleotide (FADH 2 ) oxidation and a decrease in nicotinamide-adenine dinucleotide (NADH) oxidation in hepatic mitochondria together with an increased hepatic fatty acid utilisation. 13,14,16 Taking into account that similar results were obtained by us in several experiments using rats of the same strain but from other colonies, 17 ± 19 we concluded that the strain of rats we used is very resistant to obesity between 30 and 45 d of age. Since the capacity of the rats to resist the onset of obesity tends to decrease with age, 20 it appeared of interest to verify whether this obesity resistance peculiar to young Wistar rats is maintained with increasing age.…”
Section: Introductionsupporting
confidence: 69%
“…13 ± 15 We also suggested that a contribution to the increased energy expenditure could be given by the liver, as we found an increase in avin-adenine dinucleotide (FADH 2 ) oxidation and a decrease in nicotinamide-adenine dinucleotide (NADH) oxidation in hepatic mitochondria together with an increased hepatic fatty acid utilisation. 13,14,16 Taking into account that similar results were obtained by us in several experiments using rats of the same strain but from other colonies, 17 ± 19 we concluded that the strain of rats we used is very resistant to obesity between 30 and 45 d of age. Since the capacity of the rats to resist the onset of obesity tends to decrease with age, 20 it appeared of interest to verify whether this obesity resistance peculiar to young Wistar rats is maintained with increasing age.…”
Section: Introductionsupporting
confidence: 69%
“…In fact, rats fed a high-fat diet have enhanced serum free triiodothyronine (T 3 ) levels, 5 and it is well known that T 3 stimulates the oxidation of fatty acids. 30 In addition, in rats fed a high-fat diet serum levels of free fatty acids (FFA) are higher than in controls, 6 and FFA are natural ligands of peroxisome proliferator-activated receptors (PPARs). 31 Since PPARa, which is expressed both in liver and skeletal muscle, regulates the transcription of genes coding for enzyme of mitochondrial fatty acid oxidation pathway, ie carnitine palmitoyltransferase I, 32 it can be speculated that increased FFA could directly stimulate their own oxidation via PPARs, both at liver and muscular level.…”
Section: Discussionmentioning
confidence: 99%
“…As for liver contribution to the response to high-fat feeding, we have found an increase in hepatic fatty acid oxidation rates in rats fed high-fat diet. 5,6 Concerning skeletal muscle, several studies have found changes in mitochondrial enzyme activities in rats fed a high-fat diet. 9 -12 However, to our knowledge none of these studies has dealt with changes in the whole tissue oxygen consumption, which is a more direct index of muscle metabolic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is known that diets rich in fat are generally associated with the development of obesity (Smith et al 1998;Hill et al 2000). However, it has been previously shown that post-weaning (about 30-d-old) and post-pubertal (about 50-d-old) rats fed a high-fat diet for 2 weeks exhibit increased energy intake associated with increased energy expenditure, which exceeds the obligatory cost of energy gain (Liverini et al 1996;Iossa et al 1999a). This regulatory increase in thermogenic capacity counteracts obesity development completely in post-weaning rats but only in part in post-pubertal rats, thus suggesting a weakness of regulatory responses to increased fat intake during growth.…”
mentioning
confidence: 99%